1972
DOI: 10.1071/ph720387
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Emission Processes in a Magnetoactive Plasma

Abstract: Plasma emission (i.e. emission at about the plasma frequency and twice this frequency) is treated taking into account the effects of the magnetic field on the electron plasma waves, on the conversion processes, and on the escaping radiation. The expected degrees of polarization of the fundamental and second harmonic are calculated in the weak field limit. The results are used to estimate the magnetic field strength B at the 80 MHz level from the observed polarization of type III bursts; the result B < 0·04 G i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
1

Year Published

1973
1973
2014
2014

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 96 publications
(50 citation statements)
references
References 6 publications
1
48
1
Order By: Relevance
“…Wentzel (1984) therefore proposed that the emission was depolarised to some extent within the source region itself, and that this was inherent to the emission process. For harmonic emission, it was initially thought that the Langmuir waves involved would coalesce head on, and therefore Melrose & Sy (1972); Melrose et al (1978) and the correction by Melrose et al (1980) concluded that harmonic emission must be weakly O-mode polarised. Later work by Willes & Melrose (1997) showed that relaxing the head-on condition allowed stronger polarisation, with less restriction on the participating Langmuir waves.…”
Section: Polarisationmentioning
confidence: 99%
“…Wentzel (1984) therefore proposed that the emission was depolarised to some extent within the source region itself, and that this was inherent to the emission process. For harmonic emission, it was initially thought that the Langmuir waves involved would coalesce head on, and therefore Melrose & Sy (1972); Melrose et al (1978) and the correction by Melrose et al (1980) concluded that harmonic emission must be weakly O-mode polarised. Later work by Willes & Melrose (1997) showed that relaxing the head-on condition allowed stronger polarisation, with less restriction on the participating Langmuir waves.…”
Section: Polarisationmentioning
confidence: 99%
“…A low degree of polarization is possible, provided that the magnetic field in the source regions is sufficiently weak (Melrose & Sy 1972), but the values ( T1 G) required are implausible. For a more plausible value for the magnetic field, depolarization is required, and Benz & Zlobec (1978) suggested depolarization at a quasi-transverse (QT) region (see x 4.4).…”
Section: Type III Emissionmentioning
confidence: 99%
“…where ε i j , ω, and k are the tensor of dielectric permeability, frequency, and wave vector for the considered wave type, respectively. The parameter R(k) is determined by (Melrose & Sy 1972;Willes & Robinson 1996) R(k) = ω ∂(ω 2 )/∂ω , = a * i (k)ε i j (ω, k)a j (k).…”
Section: Resultsmentioning
confidence: 99%